2007
DOI: 10.1007/s10682-007-9174-8
|View full text |Cite
|
Sign up to set email alerts
|

Pollen competition and environmental effects on hybridization dynamics between Phlox drummondii and Phlox cuspidata

Abstract: Pollen competition between species strongly influences hybridization dynamics in plants. By performing single-and mixed-donor pollinations, we show that soil Ca alters the outcome of interspecific pollen competition in the annual Phlox hybrid system of Phlox cuspidata and P. drummondii. In the absence of interspecific pollen competition, heterospecific pollen siring success of both species was influenced most strongly by the maternal growth environment, such that hybridization was facilitated when heterospecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Some studies just assume that hybrids are maladapted as a result of apparent differential local adaptation of the parents (McNeilly & Antonovics, 1968;Silvertown et al, 2005;Zeng et al, 2011). In the Phlox system, hybrids between P. cuspidata and P. drummondii are vigorous, but suffer low fertility (0-30% compared with nonhybrid individuals), indicating a high cost to hybridization (Ruane & Donohue, 2008).…”
Section: Mating Costmentioning
confidence: 99%
“…Some studies just assume that hybrids are maladapted as a result of apparent differential local adaptation of the parents (McNeilly & Antonovics, 1968;Silvertown et al, 2005;Zeng et al, 2011). In the Phlox system, hybrids between P. cuspidata and P. drummondii are vigorous, but suffer low fertility (0-30% compared with nonhybrid individuals), indicating a high cost to hybridization (Ruane & Donohue, 2008).…”
Section: Mating Costmentioning
confidence: 99%
“…It has been suggested that this pattern is caused by reinforcement (Levin 1985). Hybrids between the two species are largely, though not completely, sterile (Levin 1967;Ruane and Donohue 2008), thus allowing for some introgression between the species (Levin 1975). Moreover, there is experimental evidence indicating that dark-red-flowered P. drummondii experience less interspecific hybridization than light-blue-flowered individuals (Levin 1985).…”
mentioning
confidence: 99%
“…While effects on male function are less studied, evidence is accumulating that both individual components of male reproductive success (Rao et al 1992;Havens et al 1995;Demchik and Day 1996;Agrawal et al 1999;Lehtila and Strauss 1999;Galen 2000;Pendleton 2000;Galloway 2001;Poulton et al 2001aPoulton et al , b, 2002Etterson and Galloway 2002;Avila-Sakar et al 2003;Galen and Stanton 2003;Hedhly et al 2005;Kravetz et al 2008) and overall ability to sire seeds (Young and Stanton 1990;Lau and Stephenson 1993;Quesada et al 1995;Delph et al 1997;Johannsen and Stephenson 1998;Poulton et al 2001a;Pasonen et al 2002;Hersch 2006;Ruane and Donohue 2008) vary as environments change.…”
Section: Discussionmentioning
confidence: 99%
“…ability of pollen donors to sire seeds. Seed paternity has been shown to be significantly affected by soil nutrient composition (Young and Stanton 1990;Lau and Stephenson 1993;Poulton et al 2001a;Ruane and Donohue 2008), the presence of mycorrhizae (Poulton et al 2001a), variation in temperature (Johannsen and Stephenson 1998;Pasonen et al 2002), and herbivory (Quesada et al 1995;Avila-Sakar et al 2003;Hersch 2006; but see Strauss et al 2001).…”
Section: Introductionmentioning
confidence: 99%